Conference Report: 'Peter Larkin: Poetry, Phenomenology, and Ecology', 26th of April 2017, University of Warwick. Issue 1 (19th July 2019) - de Sousa, Gabriel
Abstract : This is a report detailing the 'Peter Larkin: Poetry, Phenomenology, and Ecology' symposium which took place at the University of Warwick on 26th of April 2017. It functions as an introduction to a forthcoming special issue of the Journal of British and Irish Innovative Poetry of articles based on the proceedings of the symposium, guest edited by Professor Emma Mason of the University of Warwick.